THE ROLE OF WORK STRESS IN MARRIAGE COMMITMENT AMONG POLICE PERSONNEL: A SYSTEMATIC LITERATURE REVIEW - Wasono, Andy; Arinata, Firdian Setiya; Awalya, Awalya; Septyanti, Ernest Ceti; Isrofin, Binti; Sutarto, Joko (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
Work stress in police personnel is one of the important factors influencing psychological well being and family dynamics, particularly marital commitment. This study aims to identify and analyze the relationship between work stress and marital commitment among Indonesian National Police personnel thru a systematic literature review (SLR) approach to recent national and international research. The study results indicate that work stress has an impact on reducing communication quality, causing role conflict, and increasing emotional tension in the marital relationships of police personnel. Work-family conflict is the main mediator in this relationship. While social support, flexible work policies, and individual coping strategies are important moderating factors in overcoming existing conditions. The limitations of the research found are primarily related to the dominance of quantitative studies, the limitations of the local Indonesian context, and the scarcity of longitudinal studies, which pose challenges for the development of effective interventions. This study recommends strengthening organizational and family support and developing policies responsive to the dynamics of work stress to improve resilience and the quality of marital commitment among police personnel. This finding is very important in efforts to strengthen understanding of the work-life balance in the police environment in order to support the professionalism and well-being of members and their families.